Increasing antimicrobial resistance is not inevitable: in reply to microbiological and antibiotic profile of osteomyelitis tertiary care hospital - Corrigan, Ruth A.; Dudareva, Maria; McNally, Martin (International Surgery Journal, 2021)
It was with interest and alarm that we read the report by Vijakumar et al regarding antimicrobial susceptibility patterns of pathogens isolated from patients with chronic osteomyelitis.1 The authors reviewed 132 isolates from 100 patients managed in Davangere, Karnataka, South West India between January 2017-December 2019.